Evidence for treatable inborn errors of metabolism in a cohort of 187 Greek patients with autism spectrum disorder (ASD) - Spilioti, Martha; Evangeliou, Athanasios; Tramma, Despoina; Theodoridou, Zoe; Metaxas, Spyridon; Michailidi, Eleni; Bonti, Eleni; Frysira, Helen; Haidopoulou, Katerina; Asprangathou, Despoina; Tsalkidis, Aggelos; Kardaras, Panagiotis; et al. (Frontiers in Human Neuroscience, 2013)
We screened for the presence of inborn errors of metabolism (IEM) in 187 children (105 males; 82 females, ages 4 -14 years old) who presented with confirmed features of ASD. Twelve patients (7%) manifested increased 3-hydroxyisovaleric acid (3-OH-IVA) excretion in urine, and minor to significant improvement in autistic features was observed in seven patients following supplementation with biotin. Five diagnoses included: Lesch Nyhan syndrome (2), succinic semialdehyde dehydrogenase (SSADH) deficiency (2) and phenylketonuria (1) (2.7%). Additional metabolic disturbances suggestive of IEMs included two patients whose increased urine 3-OH-IVA was accompanied by elevated methylcitrate and lactate in sera, and 30 patients that showed abnormal glucose-loading tests. In the latter group, 16/30 patients manifested increased sera beta hydroxybutyrate (b-OH-b) production and 18/30 had a paradoxical increase of sera lactate. Six patients with elevated b-OH-b in sera showed improved autistic features following implementation of a ketogenic diet. Five patients showed decreased serum ketone body production with glucose loading. Twelve of 187 patients demonstrated nonspecific MRI pathology, while 25/187 had abnormal EEG findings. Finally, family history was positive for 22/187 patients (1st or 2nd degree relative with comparable symptomatology) and consanguinity was documented for 12/187 patients. Our data provide evidence for a new biomarker (3-OH-IVA) and novel treatment approaches in ASD patients. Concise 1 sentence take-home message: Detailed metabolic screening in a Greek cohort of autismspectrum disorder (ASD) patients revealed biomarkers (urine 3-hydroxyisovaleric acid and serum b-OH-b) in 7% (13/187) of patients for whom biotin supplementation or institution of a ketogenic diet resulted in mild to significant clinical improvement in autistic features.